Vibration based moving inspection method to detect loose fasteners and damaged supports in a rail system - Wang, Longqi (2017)
A rail system is the most important land transportation. Its safety and stability are critical. The rails are installed on discrete supports. In practice, there are several defects, such as loosening of fasteners and degradation of sleepers and blasters, frequently occurred on these supports. Currently, the detection of defects relies mainly on visual inspection by trained personal. This study proposes a workable solution to detect these defects in view of their significant influences on the support stiffness between the rails and the discrete supports. The method only requires one sensor mounted on a moving device. Based on the numerical and experimental examples, degraded supports are located accurately, irrespective of the spatial distribution of degraded supports. The method performs well under periodic impact and random excitation and is far more efficient and accurate than visual inspection.